Reproductive pathophysiology of bucks post-challenged with Mannheimia haemolytica A2 and its immunogens lipopolysaccharide and outer membrane protein - Azhar, Nur Amira (2022)
Pneumonic mannheimiosis is a bacterial respiratory disease caused by Mannheimia haemolytica serotype A2 in sheep and goats. This disease had led to significant economic losses to the small ruminant industries worldwide including Malaysia, mainly due to its high mortality and morbidity rate. The M. haemolytica A2 is a Gram-negative, weakly haemolytic bacterium residing in the upper respiratory tract of healthy animals as commensals. It may eventually gain access to the lower respiratory tract when the immune system is compromised and cause further damage to the lung tissues. The pathogenicity of M. haemolytica A2 is triggered by its numerous virulence factors which include the lipopolysaccharide (LPS) and outer membrane protein (OMP), which in turn may trigger host systemic inflammatory responses. While its role in causing a respiratory infection is evident, its potential impact on the reproductive system remains uncovered. Hence, this study was conducted to investigate the potential impact of the infection from M. haemolytica A2 and its immunogens LPS and OMP on the reproductive functions of infected bucks. A total of 16 clinically healthy, crossbred bucks aged 1.5-2 years old were used in this study. The bucks were randomly assigned into four groups of four bucks each. Bucks in Group 1 (control group) were intranasally inoculated with 2 mL of PBS pH 7.0, Group 2 with 2 mL of 1.2 X 109 CFU/mL M. haemolytica A2 intranasally, Group 3 with 2 mL of LPS endotoxin extracted from 1.2 X 109 CFU/mL M. haemolytica A2 intravenously and Group 4 with 2 mL of OMP extracted from 1.2 X 109 CFU/mL M. haemolytica A2 intramuscularly. Bucks were closely monitored for clinical responses post-challenge throughout the study, which include changes in temperature, heart rate, respiratory rate, rumen motility, lung sound, and presence of nasal discharge. Blood samples were obtained via jugular venipuncture into 5 mL plain tubes and the sera harvested at pre-determined intervals were used to determine the pro-inflammatory cytokines (IL1β, IL6, TNFα, and IFNγ), heat shock proteins (HSP70, HSP90), toll-like receptors (TLR2, TLR4) and reproductive hormones (testosterone, LH) responses. Semen quality was also examined to determine the effect of treatments on bucks by evaluating the changes in sperm motility, viability, wave pattern, and abnormal morphology. Ejaculates were collected by using an electro-ejaculator and were analyzed promptly after collection. The experimental bucks were euthanized via exsanguination on Day 60 post-challenge and the organs were examined grossly at necropsy. Tissue samples from the vital organs (lung, liver), reproductive organs (testis, epididymis, vas deferens, prostate), and lymph nodes (bronchial, iliac) were also obtained and processed by using a common H&E protocol to be analyzed and scored under light microscopy. All experimental bucks from Groups 1, 2, 3, and 4 survived until the end of the study. This study revealed that the administration of M. haemolytica A2 and its immunogens, LPS and OMP may induce clinical responses similar to natural infection of pneumonic mannheimiosis such as fever, increased heart rate and respiratory rate, rumen hypomotility and nasal discharge in experimental bucks. Serum analyses then showed a significant increase in serum IL1β, IL6, TNFα and IFNγ concentrations in all treatment groups, particularly in Group 3 bucks by 1h and were prominent within the first 12 hours post-challenge, indicating the activation of host systemic inflammatory responses. HSP70 and HSP90 levels were also increased post-challenge in Groups 2, 3 and 4 bucks with the highest fold increase recorded was a 2.5-fold increase in HSP90 level in Group 3. The serum levels of pro-inflammatory cytokines and heat shock proteins gradually decreased approaching Day 56 of this study. These increases were also accompanied by increased concentrations of TLR2 and TLR4, a vital receptor for OMP and LPS, respectively, as early as 1h post-challenge. The serum TLR2 in Group 4 and the serum TLR4 in Groups 2 and 3 remained higher than in Group 1 until the end of the study, signifying the activation of inflammatory responses by these immunogens that result in the release of pro-inflammatory cytokines. Moreover, of both reproductive hormones examined in this study, only the testosterone hormone showed an evident decrease in serum concentrations, mainly in Groups 3 and 4 and a slight reduction in Group 2 as compared to Group 1 which lasted until day 56. In contrast, the only significant changes in serum concentration of LH were recorded at 1h and 12h in Groups 2 and 3, respectively, indicating that the administration of M. haemolytica A2 and its LPS and OMP in experimental bucks may influence the concentration of reproductive hormones to a varying degree. Likewise, a significant reduction in sperm motility, percentage viability, wave pattern and increased morphological abnormalities were observed as early as 1d post-challenge and were evident across groups, particularly in Group 3 within the first 35 days before it normalizes with Group 1 approaching Day 56 of the study. While the reproductive organs and lymph nodes appeared normal grossly at necropsy, the lung and liver of bucks from Groups 2, 3 and 4 displayed mild gross lesions. Histopathological analysis revealed changes in the reproductive organ which highlight the potential effect of M. haemolytica A2 on the reproductive functions of infected bucks. The lesion scoring of the reproductive organs, vital organs and lymph nodes ranged from mild to moderate lesions across the groups, mostly for necrosis and degeneration. These changes persisted until the end of a study, suggesting that it may require more than one spermatogenic cycle for infected bucks infected to regain optimal reproductive functions post-infection. Therefore, the results obtained in this study indicate that besides affecting the respiratory system of infected animals as previously reported, the experimental administration of M. haemolytica A2 and its LPS and OMP induced inflammatory responses and may affect the reproductive functions of bucks by altering the reproductive hormone levels and sperm parameters. This would be the first study reporting the potential effect of M. haemolytica bacterial respiratory disease on the reproductive function of bucks, assisted by its immunogens LPS and OMP.